2006
DOI: 10.1089/acm.2006.12.1015
|View full text |Cite
|
Sign up to set email alerts
|

Human Psychophysiology, Macroscopic Information Entanglement, and the Placebo Effect

Abstract: For the past 20 years, the magnitude of the "placebo effect" in double-blind, medical experiments has strongly increased. This paper asks why and how. Starting with the human "psychophysiologic principle," two unconscious and one conscious biofeedback examples are given to demonstrate how malleable we humans are to our expectations and our intentions and how strong our psychoenergetic forces can be relative to conventional chemical forces. Ending with several experimental examples wherein a therapeutically pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…If Wallach's idea is correct, then explanatory models of placebo effects must include not only PNI considerations, but also nonlocal relationships between treatments and controls. Similar entanglement ideas have been proposed recently by Tiller 7 and by Bengston and Moga. 8 Here we propose another possible factor that may modulate placebo effects: What if the goal-oriented nature of the placebo effect were understood as a form of final cause, (e.g., as a teleological pull from our own future?)…”
Section: Introductionsupporting
confidence: 70%
“…If Wallach's idea is correct, then explanatory models of placebo effects must include not only PNI considerations, but also nonlocal relationships between treatments and controls. Similar entanglement ideas have been proposed recently by Tiller 7 and by Bengston and Moga. 8 Here we propose another possible factor that may modulate placebo effects: What if the goal-oriented nature of the placebo effect were understood as a form of final cause, (e.g., as a teleological pull from our own future?)…”
Section: Introductionsupporting
confidence: 70%
“…Indeed, the placebo effect has been described as the most effective intervention known to science; having been subjected to more clinical trials than any other intervention, usually surpassing expectations of effectiveness, and being effective against an apparently limitless range of conditions [123,124]. It is reported that the magnitude of the placebo effect in double-blinded randomised controlled trials has markedly increased since the mid 1980s [125]; now being capable of reducing symptoms by a mean of 35% [120]. Despite such claims, results of meta-analyses evaluating the existence of a placebo effect are contradictory [122,126].…”
Section: Health Carementioning
confidence: 99%
“…As background support for this effect, the work of Tiller and his associates has provided both a solid experimental and theoretical framework to demonstrate that mind/emotion action by humans can manifest as significant property changes in physical reality. [24][25][26][27] Carefully controlled scientific research proved that focused human intention can, for example, modulate the chemical properties of water molecules, increase the speed of biochemical reactions occurring in living biological tissues, alter the subconscious arousal-state of other human beings, or even skew the data processing activity of computerized random number generators (reviewed in Radin and McTaggart 28,29 ). In NMT therapy, the purpose of the pathway language is to assist the practitioner in bringing clearly to mind the concep-tual meaning of the various pathway query and corrective intentions so that he/she may iconographically project this meaning to the patient at an OTC level.…”
Section: Discussionmentioning
confidence: 99%